Analysis of Erosion Properties of Polymer Composite Filled with Granite Dust for Hydraulic Turbine Blade Material. - Joy Mathavan, J.; Shrestha, S.; Kaifi, R.; Patnaik, A (Springer Nature Singapore, 2018)
The main objective of this research work is to introduce a new material for hydraulic turbine blade for efficient usage of hydraulic energy. Instead of the usual alloys used for hydraulic turbine blades, composite material has been tested in this paper. Polyamide needle fibre (aramid fibre) has been used here; due to its high resistivity to erosion by water, it is cheap among other fibres while polyester resin was used as the matrix. The samples were prepared by hand lay-up process. As a new trend and considering waste matter utilization, granite dust was added to the above composite as a filler material, because it is considered as an industrial waste. It belongs to the igneous rock family and is found to have good mechanical properties. In different percentages, granite dust was added to the composite to test the improvement in the erosion resistance and other mechanical properties. The velocity of jet, the feed rate of erodent (silica sand), the size of erodent, and the angle of impingement were changed, and the tests were done in Taguchi standard L25 table with five variables and five factors. The results are analysed and plotted in graphs. Hardness number was calculated in Rockwell hardness tester. Theoretical and experimental densities were also calculated.
Keywords: Polyamide needle fiber; Slurry jet erosion; Granite dust